Organic Polymers for Encapsulation of Drugs, Food Ingredients and Agrochemicals - Picos Corrales, Lorenzo Antonio; Licea-Claverie, Angel; Crini, Grégorio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Reprint Book provides recent studies addressing encapsulation systems for active compounds (e.g., drugs and food ingredients) to improve the quality of life around the world. The content may be helpful for the colleagues and students working on encapsulation of active compounds.